The Friends of Cancer Research Real‐World Data Collaboration Pilot 2.0: Methodological Recommendations from Oncology Case Studies. Issue 1 (11th November 2021) - Rivera, Donna R.; Henk, Henry J.; Garrett‐Mayer, Elizabeth; Christian, Jennifer B.; Belli, Andrew J.; Bruinooge, Suanna S.; Espirito, Janet L.; Sweetnam, Connor; Izano, Monika A.; Natanzon, Yanina; Robert, Nicholas J.; Walker, Mark S.; et al.
Abstract : The purpose of this study was to evaluate the potential collective opportunities and challenges of transforming real‐world data (RWD) to real‐world evidence for clinical effectiveness by focusing on aligning analytic definitions of oncology end points. Patients treated with a qualifying therapy for advanced non‐small cell lung cancer in the frontline setting meeting broad eligibility criteria were included to reflect the real‐world population. Although a trend toward improved outcomes in patients receiving PD‐(L)1 therapy over standard chemotherapy was observed in RWD analyses, the magnitude and consistency of treatment effect was more heterogeneous than previously observed in controlled clinical trials. The study design and analysis process highlighted the identification of pertinent methodological issues and potential innovative approaches that could inform the development of high‐quality RWD studies.